Integracja koncepcji target costing i kaizen costing skuteczną metodą strategicznego zarządzania kosztami - Solak, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In todays competitive environment if the company wants to reach strategic targets it is necessary to manage costs effectively and intelligently. It is just necessary to develop strategic cost management. Joint Target Costing and Kaizen Costing Method can be a signifacant tool. Target Costing is a cost management concept which has been widely used by Japanese companies since the 1970s. Its most important aspect is marking new product costs in a planning stage of product life cycle as a market price minus required profit margin and than reducing costs to a desired level. Kaizen Costing can be very helpful in this. It is a process of cost reduction during the manufacturing phase of a product. The Japanese word kaizen refers to continual and gradual improvement through small betterment activities rather than large or radical improvement made through innovation or large investments in technology. Joint Target Costing and Kaizen Costing Method lead to costs reduction in the life cycle of the whole product. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 412-418